2013
DOI: 10.1002/jbm.a.34565
|View full text |Cite
|
Sign up to set email alerts
|

Neural responses to electrical stimulation on patterned silk films

Abstract: Peripheral nerve injury is a critical issue for trauma patients. Following injury, incomplete axon regeneration or misguided axon innervation into tissue will result in loss of sensory and motor functions. The objective of this study was to examine axon outgrowth and axon alignment in response to surface patterning and electrical stimulation. To accomplish our objective, metal electrodes with dimensions of 1.5 mm × 4 cm, were sputter coated onto micropatterned silk protein films, with surface grooves 3.5 μm wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
39
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 42 publications
(40 citation statements)
references
References 89 publications
1
39
0
Order By: Relevance
“…3336 Different strategies encompassing physical approaches, architectural designs, bioactive molecule release, genetic engineering and synergism among these features have been evaluated to achieve control over cell fate. 4,4145,57,58 …”
Section: Discussionmentioning
confidence: 99%
“…3336 Different strategies encompassing physical approaches, architectural designs, bioactive molecule release, genetic engineering and synergism among these features have been evaluated to achieve control over cell fate. 4,4145,57,58 …”
Section: Discussionmentioning
confidence: 99%
“…These changes showed heterogeneous responses among individual neurons, potentially reflecting the complexity of local circuitries and dynamics of signal propagation [4750] . Our previous study showed that chronic electrical stimulation via silk film-supported interface can promote neurite outgrowth and alignment [51] . A neural circuit model on a dish, which is similar to the microfluidic system developed on the silk film in this study, has demonstrated functional connectivity of patterned neural networks [30] .…”
Section: Discussionmentioning
confidence: 99%
“…There is a need for new sources of matrices for tissue engineering that could overcome both the limitations of synthetic and naturally extracted materials. Recently, the excellent material properties of silk proteins originated from silkworms and spiders, have drawn increased attention from tissue engineers to investigate their potential as biomaterials for tissue regeneration[22, 23]. …”
Section: Introductionmentioning
confidence: 99%